2020
DOI: 10.1109/tac.2020.2969718
|View full text |Cite
|
Sign up to set email alerts
|

Robust Feedback Stabilization of Linear MIMO Systems Using Generalized Homogenization

Abstract: A robust nonlinear control is designed for stabilizing linear MIMO systems. The presented control law homogenizes a linear system (without its transformation to a canonical form) with a specified degree and stabilizes it in a finite time (or with a fixed-time attraction to any compact set containing the origin) if the degree of homogeneity is negative (positive). The tuning procedure is formalized in LMI form. Performance of the approach is illustrated by numerical and experimental examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 28 publications
0
84
0
Order By: Relevance
“…In [31] it is shown that the system (14) can be homogeneously stabilized with a degree µ = 0 if and only if the pair {A, B} is controllable (or, equivalently, rank(B, AB, ..., A n−1 B) = n. We refer the reader to [32] for more details about controllability of linear plants. The following theorem is the corollary of a more general theorem proved [20] for evolution system in Hilbert spaces (see also [31] for more details about the finite dimensional case).…”
Section: Homogeneous Stabilization Of Linear Mimo Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [31] it is shown that the system (14) can be homogeneously stabilized with a degree µ = 0 if and only if the pair {A, B} is controllable (or, equivalently, rank(B, AB, ..., A n−1 B) = n. We refer the reader to [32] for more details about controllability of linear plants. The following theorem is the corollary of a more general theorem proved [20] for evolution system in Hilbert spaces (see also [31] for more details about the finite dimensional case).…”
Section: Homogeneous Stabilization Of Linear Mimo Systemsmentioning
confidence: 99%
“…where the canonical homogeneous norm If A 0 is nilpotent, then (16) has a solution with respect to G d [31], such that G d is anti-Hurwitz matrix. The feasibility of (17) is proven in [18] and refined in [31]. The proof of the latter theorem follows from the following computations…”
Section: Homogeneous Stabilization Of Linear Mimo Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [20], it is shown that the system (9) can be homogeneously stabilized with a degree µ = 0 if and only if the pair {A, B} is controllable (or, equivalently, rank(B, AB, ..., A n−1 B) = n. We refer the reader to [21] for more details about controllability of linear plants. The following theorem is the corollary of a more general theorem proven in [17] for evolution system in Hilbert spaces (see also [20] for more details about the finite dimensional case).…”
Section: A Homogeneous Stabilization Of Linear Mimo Systemsmentioning
confidence: 99%
“…where F T is assumed to be close to mg and the angle θ, φ are assumed to be close to 0. Denoting ζ = (x, y,ẋ,ẏ, θ, −φ,θ, −φ) from (21) and (20) we derivė…”
Section: Linear and Homogeneous Controllersmentioning
confidence: 99%